Single and combined effects of beetroot crystals and sodium bicarbonate on 4-km cycling time trial performance - Callahan, M. J.; Parr, E. B.; Hawley, J. A.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
When ingested alone, beetroot juice and sodium bicarbonate are ergogenic for high-intensity exercise performance. This study sought to determine the independent and combined effects of these supplements. Eight endurance trained (VO2max 65 mL·kg·min-1) male cyclists completed four × 4-km time trials (TT) in a doubleblind Latin square design supplementing with beetroot crystals (BC) for 3 days (15 g·day-1 + 15 g 1 h before TT, containing 300 mg nitrate per 15 g), bicarbonate (Bi 0.3 g·kg-1 body mass [BM] in 5 doses every 15 min from 2.5 h before TT); BC+Bi or placebo (PLA). Subjects completed TTs on a Velotron cycle ergometer under standardized laboratory conditions. Plasma nitrite concentrations were significantly elevated only in the BC+Bi trial before the TT (1520 ± 786 nmol·L-1) compared with baseline (665 ± 535 nmol·L-1, p = .02) and the Bi and PLA conditions (Bi: 593 ± 203 nmol·L-1, p < .01; PLA: 543 ± 369 nmol·L-1, p < .01). Plasma nitrite concentrations were not elevated in the BC trial before the TT (1102 ± 218 nmol·L-1) compared with baseline (975 ± 607 nmol·L-1, p > .05). Blood bicarbonate concentrations were increased in the BC+Bi and Bi trials before the TT (BC+Bi: 30.9 ± 2.8 mmol·L-1; Bi: 31.7 ± 1.1 mmol·L-1). There were no differences in mean power output (386-394 W) or the time taken to complete the TT (335.8-338.1 s) between any conditions. Under the conditions of this study, supplementation was not ergogenic for 4-km TT performance.